PENGARUH LOCUS OF CONTROL, GAYA KEPEMIMPINAN, KOMITMEN ORGANISASI DAN PEMAHAMAN GOVERNANCE TERHADAP KINERJA AUDITOR (Studi Empiris Pada Kantor Inspektorat Provinsi Riau) - Fazlan Hady Rohiddatul; Azwir Azwir; Riska Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of locus of control, leadership style, organizational commitment and understanding of governance on auditor performance. This research was conducted based on the findings of problems related to auditor performance. The population of this research is the Inspectorate of Riau Province. The sample selection in this study used a census method, so that the entire population was sampled, namely 40 samples. The data analysis used in the study was SPSS 17, while the data used was a questionnaire that had been filled in by auditors working at the Inspectorate of Riau Province. The results show that 1) locus of control affects the performance of auditors, 2) leadership style affects auditor performance, 3) organizational commitment affects auditor performance, 4) understanding of governance does not affect auditor performance.Keywords: Locus of Control, Leadership Style, Organizational Commitment and Understanding of Governance on Auditor Performance